Effect of different doses of sodium fluoride on various hydroxyproline fractions in rat serum - Siddiqi, N. J.; Al omireeni, E. A.; Alhomida, A. S. (Cellular and Molecular Biology, 2011)
Human beings are exposed to fluoride through its occurrence in the environment and its presence in various products. The present study was carried out to study the effect of acute doses of sodium fluoride on the body collagen in rats. To evaluate this effect the concentration of collagen breakdown products like different hydroxyproline fractions were determined in serum following the exposure of rats to various concentrations of sodium fluoride. 5 and 10 mg/kg weight dose of NaF caused no significant change in total hydroxyproline but caused significant changes in some of the hydroxyproline fractions. However higher doses of NaF viz., 20 and 30 mg/kg body weight caused significant changes in different hydroxyproline fractions and also a significant decrease in total hydroxyproline indicating the probability of collagen formation in some tissues.